Bibliometric Analysis of Nanomedicine Application in Parkinson's Disease using VOSviewer - Andre Safrie Maulana (Komunitas Menulis dan Meneliti (Kolibi), 2023)
Nanomedicine is a drug that has a size in the range of 1 – 100 nm. Nano-sized drugs can be applied as drug delivery agents by encapsulating or binding the active substance which then delivers the active substance to controlled tissue. Parkinson's disease is a disease caused by the loss of dopaminergic cells in the midbrain, so the treatment of Parkinson's disease is to provide increased dopamine concentrations or stimulate dopamine receptors. This research aims to map research regarding the application of nanomedicine to Parkinson's disease from the aspects of researchers, publishers and citations. This research uses bibliometric analysis methods, the Publish or Perish search engine to search for data, and the VOSviewer application as a data mapping application. The time range used starts from 2017 to 2022, resulting in data for 284 articles. The results of this research found that the development of research regarding the application of nanomedicine to Parkinson's disease increases in publications every year, based on the highest number of citations with more than 100 citations consisting of 20 articles from various publisher sources. Meanwhile, in the co-occurrence analysis using VOSviewer, it was shown that in the network visualization the keywords that frequently appeared were